Recreational maritime fishing in the Balearic Islands: tradition and future - Grau A.M. (The Mediterranean fisheries sector. A reference publication for the VII meeting of Ministers of agriculture and fisheries of CIHEAM member countries (Zaragoza, Spain, 4 february 2008), 2008)
The Balearic Islands are the region of Spain in which recreational maritime fishing has the longeststanding tradition, social relevance and economic importance. There are about 70,000 recreational fishermen (8% of the population) that practise more than 60 different techniques, predominantly from a boat (63%) followed by coastal angling (33%). Submarine fishing, even though it is practised by a minority (4%), has a large impact on the coastal fauna. Although annual catches from recreational fishing (1200 t) are about 25% of those of the professional fleet, it is estimated that they generate an added value 4 times higher; meaning that for each kilo of fish caught, recreational fishing generates an added value 16 times higher than professional fishing. The economic, social and environmental implications of this fact are taken firmly into account in the management of the region's fishery resources. For several years, the regional Government has been implementing a series of innovative measures (vessel licences, specific close seasons, marine reserves, non-fishing days, etc.), that could serve as a sustainable management experience applicable to many other areas of the Western Mediterranean. With a view to the future, it is still necessary to apply new formulas of selective fishing, such as the introduction of minimum hook sizes, but moreover it is important to improve information and training of recreational fishermen on sustainability issues and to involve them in the management.
7. Meeting of Ministers of Agriculture and Fisheries of CIHEAM Member Countries, 2008/02/04, Zaragoza (Spain)